PENGARUH BUDAYA KERJA TERHADAP KEPUASAN KERJA APARAT DESA KAYU ANGIN KABUPATEN MAJENE - Muhammad Rivai; Syahril Syahril (Paser Institute Management and Busines, 2024)
This research discusses the influence of work culture on employee job satisfaction at Aparat desa kayu angin kabupaten majene. By using descriptive survey research methods and quantitative methods, this research found that the organizational culture implemented in the company has a significant influence on employee job satisfaction. The research results show that employees who implement the organizational culture provided by the company, such as behavioral regularity, norms, values and philosophy, have higher job satisfaction. Apart from that, salary indicators also play an important role in increasing employee job satisfaction. The results of this research contribute to further understanding of how organizational culture and compensation can increase employee job satisfaction, as well as the implications for organizational performance.